Tombs and transnational history in greater China: a collection of case studies - Müller-Saini, Gotelind (Asien, 2022)
This collection of case studies is concerned with tombs that testify to transnational history. Special attention is given to tombs of Westerners and…
Keywords: Aufsatzsammlung; Sozialgeschichte 1800-2018; Ausländer; Grab; China